Political confrontations and disagreements in the Nigerian Government’s COVID-19 response - Tahir Adekunle Ijaiya (Faculty of Social and Political Science, Universitas Airlangga, 2023)
The COVID-19 outbreak has led to various interventions and policies from governments around the world, including Nigeria. However, Nigeria’s response was laden with political interests, confrontation and disagreements from various blocs of interest. Therefore, this study aims to examine various phenomena of political confrontation and disagreement during COVID-19 intervention. This study uses qualitative methods. Data were obtained through qualitative secondary data and analyzed thematically. The results of this study indicate that the People’s Democratic Party (PDP) and the All Progressive Congress (APC) are the two political parties that engage in the most political confrontation and disagreement. This study found that conflicting interests also occurred between the government and several interest groups regarding the import of foreign health workers and the distribution of COVID-19 assistance. Similarly, disagreements also ensued between the federal government and some subnational governments over their refusal to acknowledge the existence and/or severity of COVID-19. This study concludes that political conflicts and disagreements during COVID-19 in Nigeria were caused by government policies and interventions that could not be separated from competing interests and needs of the political, business, and professional elite.